Perbandingan Tingkat Kecemasan Karir Mahasiswa Laki-Laki dan Perempuan Program Studi Bimbingan dan Konseling (Studi Komparatif) - Cantika, Maria Yesthia; Robertus Budi Sarwono (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study intended to (1) compare the differences in career anxiety levels between male and female students, (2) assess the level of career anxiety among male students, (3) determine the level of career anxiety of female students. A comparative descriptive quantitativ approach is the basis of this study. Participants in this study involved students of the Guidance and Counseling Study Program, Sanata Dharma University, class of 2021, consisting of 21 male students and 51 female students. Data collection used the career anxiety adoption scale from Samosir (2023) developed by Tsai et al. (2017). Valid items in this study numbered 24 out of a total of 25 items. The reliability coefficient value calculated using Cronbach’s Alpha was 0.817. Based on the result of the t-test, a significant difference was found in the level of career anxiety betweet male and female final year students. With an average score of 60.33 for male students and 53.37 for female students, these results indicate that male students in the Guidance and Counseling Study Program of Sanata Dharma University experience higher levels ofcareer anxiety.